Influencia de la fertilización, la época y la especie forrajera en la presencia Influence of fertilization, season, and forage species in presence of arbuscular mycorrhizae in a degraded Andisoil of Colombia - Arnulfo Gómez-Carabalí; Idupulapati M. Rao; J. Tupac Otero (Acta Agronómica)
Para determinar la influencia de la fertilización, época, y especies forrajeras en la producción de micorrizas arbusculares se realizó un experimento con una gramínea C4, (Brachiaria dictyoneura), dos leguminosas forrajeras C3 (Arachis pintoi y Centrosema macrocarpum) y la vegetación nativa; cultivadas en dos sistemas de siembra (monocultivo y asociación), dos niveles de fertilización (alto y bajo) y cuatro edades de cosecha. Se uso un diseño de parcelas sub-sub divididas, en el cual la parcela principal fue la especie, los niveles de fertilización como subparcelas y la edad de rebrote como la sub-sub parcela. El número de esporas de hongos micorrízicos en el suelo y el porcentaje de infección en las raíces se incrementó con la edad y varió con la especie y la época del muestreo (seca o húmeda). Se encontraron diferencias en la capacidad para formar simbiosis micorrízica entre las especies de gramíneas y leguminosas bajo condiciones de campo. In the Colombian coffee zone much of the land has infertile soils with an ongoing accelerated degradation. As vegetation has changed from forest to transitory base (cassava cropping) and overgrazed pastures, ground cover has decreased resulting in increasing runoff. These changes have contributed to severe erosion, decline in soil fertility, productivity, soil structure, and water quality as well as loss of biodiversity. A field study was conducted at the farm "La Esperanza" (Mondomo, Department of Cauca, Colombia, South-America). The main objective was to determine the influence of fertilization, season and forage species in Arbuscular Mycorrhyzae in a degraded Andisol. One C4 forage grass (Brachiaria dictyoneura) and two C3 forage legumes (Arachis pintoi and Centrosema macrocarpum) and native vegetation grown under two fertilization levels, cultivated either in monoculture or in association and harvested at four different ages were evaluated. The numbers of mycorrizal spores in the soil and percentage of root infection of arbuscular mycorrhiza increased with age and varied with the species and season. We founded differences among forage grass and legume species under field conditions to form symbiosis with mycorrhizal fungi. Knowledge on these interspecific differences could contribute to developing better adapted forage systems to contribute recuperating the degraded soils of the Andean hillsides of Latin America.